Public awareness and perception towards COVID-19 in Sub-Saharan African countries during the lockdown - Ekpenyong, B.N.; Abu, E.K.; Langsi, R.; Osuagwu, U.L.; Oloruntoba, Richard; Ovenseri-Ogbomo, G.; Timothy, C.G.; Charwe, D.D.; Nwaeze, O.; Goson, C.P.; Miner, C.A.; Ishaya, T.; et al. (2022)
Background: The coronavirus disease (COVID-19) outbreak has caused a universal health crisis resulting in significant morbidities and mortalities particularly among high-risk groups. This study sought to determine regional factors associated with knowledge and attitude towards COVID-19 mitigation practices and risk perception of contracting the disease in Sub-Saharan African (SSA) countries.